Fishes from Baía da Medalha, southern Pantanal, Brazil: A 20 years review - Severo-Neto, Francisco; Tencatt, Luiz Fernando Caserta; Costa-Pereira, Raul [UNESP]; Tavares, Luiz Eduardo Roland (Instituto Virtual da Biodiversidade | BIOTA - FAPESP, 2015)
Located in the Pantanal of Miranda-Abobral, the Baía da Medalha is the largest pond close to the Base de Estudos do Pantanal of the Universidade Federal de Mato Grosso do Sul. The Baía da Medalha has been a study site for several didactic and scientific projects for years. Nevertheless, its fish fauna has never been inventoried. Based on data collected from the beginning of the 1990s up to 2011, we provide a list of fish species from the Baía da Medalha. A total of 97 species were recorded, corresponding to about 40% of the species stated for the Pantanal. Characiformes and Siluriformes were the most species-rich orders, being Characidae and Cichlidae the families with the highest number of species. Regional seasonal flood dynamics and the abundance of aquatic macrophytes may be associated with this high diversity. The representative richness found in this lagoon highlights the importance of such taxonomic surveys to preserve the diversity of aquatic habitats within the Pantanal ecosystem.

Localizada no Pantanal do Miranda-Abobral, a Baía da Medalha é a maior e mais próxima lagoa da Base de Estudos do Pantanal da Universidade Federal de Mato Grosso do Sul. A Baía da Medalha tem sido área de estudo de diversos projetos didáticos e científicos há anos, entretanto, nenhum inventário sobre sua ictiofauna foi realizado. Aqui é apresentada uma lista de espécies de peixes da Baía da Medalha baseado em dados de coletas do começo da década de 90 até 2011. Um total de 97 espécies foi registrado, correspondendo è cerca de 40% do total de espécies registradas para o Pantanal. Characiformes e Siluriformes foram as ordens mais ricas em espécies, sendo Characidae e Cichlidae as famílias com maior número de espécies. Dinâmicas de inundação sazonal e a abundância de macrófitas aquáticas podem ser associadas a esta alta diversidade. A representativa riqueza encontrada nesta lagoa ressalta a importância de levantamentos taxonômicos a fim de preservar a diversidade dos habitats aquáticos do dentro do ecossistema do Pantanal.
Peixes da Baía da Medalha, Pantanal Sul, Brasil: Uma revisão de 20 anos
Keywords: Lagoon; Wetlands; Rio Miranda; Ichthyofauna; Lagoa; Áreas úmidas; Rio Miranda; Ictiofauna